Implementasi Akad Mudharabah Mutlaqah Pada Tabungan Haji IB Amanah Terhadap Profitabilitas PT Bank Pembangunan Daerah Jawa Timur Tbk. - El Nadia, Nada; Masadah,; Muhammad Yazid,; Muhammad Iqbal Surya Pratikto,; Nurul Fatma Hasan, (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study explores the implementation of mudharabah mutlaqah contracts in the IB Amanah Hajj Savings product offered by the Islamic Business Unit of Bank Jatim, and its contribution to the bank’s profitability. Using a qualitative descriptive approach, field data were collected through interviews, observation, and document analysis at Bank Jatim KCPS Sampang. The findings reveal that the application of mudharabah mutlaqah aligns with the DSN-MUI Fatwa No. 02/DSN-MUI/IV/2000 and enables the bank to profit from Hajj deposits while maintaining Sharia compliance. Over the period 2019–2021, IB Amanah contributed between 1.25% and 1.31% to the bank's net profit, with a 90:10 profit-sharing ratio favoring the bank. The study contributes to the global Islamic finance literature by demonstrating how long-term religious savings products can support the financial sustainability of regional Islamic banking institutions. It also offers a practical framework for integrating Sharia contracts into public savings mechanisms without compromising operational profitability. This case can inform international practices, especially in Muslim-majority economies aiming to optimize Hajj fund management through ethical investment strategies. Future research could compare mudharabah-based Hajj savings with other contract models (e.g., wadi’ah) across jurisdictions to assess risk-sharing efficiency and depositor trust in Islamic financial institutions.